Factors related to medication adherence in patients with type 2 diabetes based on the MARS-10 scale - Nguyen, Thi Xuan Tam; Ngo, Thi Kim Cuc; Le, Thi Thanh Tinh; Nguyen, Thi Hai Yen; Nguyen, Thi To; Le, Chuyen (Tạp chí Y Dược Huế, 2025)
Introduction: Medication adherence directly affects glycemic control and clinical outcomes. Factors related to medication adherence tend to be complex due to interactions between medication, patients, and healthcare professionals. Objectives: To investigate medication adherence rate and factors related to medication adherence in patients with type 2 diabetes. Subjects and Methods: A cross-sectional study was conducted, interviewing 394 patients at the Internal Medicine Clinic, Hue University of Medicine and Pharmacy Hospital, from July 2022 to July 2023, using the MARS-10 questionnaire. Results: The medication adherence rate was 81.7%. Factors associated with medication adherence included HbA1c target (p = 0.025), reminders from healthcare professionals (p = 0.028), and monthly follow-up visits (p = 0.027). Conclusion: Measures are needed to enhance counseling and education to remind patients about medication use and glycemic control at home.